(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article examines the intersection of Chingiz Aytmatov Street and the Small Ring Road in Tashkent as the object of study. It analyzes the intensity of traffic flow in this area as well as the impact of the existing road infrastructure on traffic safety. Additionally, practical recommendations and proposals have been developed to address the identified problems.